(untitled) (Asian Journal of Medical and Biological Research, 2022)
The present research was conducted to assess the mosquito larvicidal potential of selected medicinal plants using an effective but simple method. Aqueous extracts of roots of three selected medicinal plants viz. Derris scandens, Rubia cordifolia and Saussurea lappa were evaluated for their mosquito larvicidal potential against the 3rd instar larvae of C. quinquefasciatus Say (1823) under laboratory settings. Aqueous extracts of these plants at seven different concentrations (1, 25, 50, 100, 150, 200 and 300 ppm) exhibited considerable mortality of the 3rd instar larvae after 24 and 48 h exposure. Among the plants, D. scandens root extract exhibited the highest toxicity inducing 100% larval mortality after 24 h exposure at 250 ppm concentration, followed by the root extracts of R. cordifolia and S. lappa inducing 98.4% and 87.8% larval mortality, respectively. Overall, extracts of all the plants exhibited a strong positive correlation between the concentration of extracts and larval mortality (p˂0.001) with a correlation coefficient of more than 0.90. The LC50 and LC90 values after 24 h contact demonstrated D. scandens as the most toxic with the lowest LC50 and LC90 values (LC50=78.20 ppm, LC90=147.33 ppm) followed by R. cordifolia (LC50= 89.32 ppm, LC90=204.09 ppm) and S. lappa (LC50=112.29 ppm, LC90=248.72 ppm), respectively. Our results clearly indicated that all the plants’ aqueous extracts showed considerable larvicidal potential against the 3rd instar larvae of C. quinquefasciatus. To conclude, the application of aqueous extracts from these plants to larval habitats may efficiently control C. quinquefasciatus mosquitoes, hence, can be recommended as a potential alternative to chemical insecticides against these vectors. Asian J. Med. Biol. Res. 2022, 8 (4), 187-193